Sistem Buka Tutup Kaca Helm Menggunakan Voice Recognition Berbasis Mikrokontroler - Muhammad Basri; Asrul Asrul; Farid Hidayat (Fakultas Teknik Universitas Muhammadiyah Parepare, 2025)
Technology in vehicle helmets has developed rapidly to improve safety, comfort, and the driving experience for users. Development research using the Research and Development method. The system designed uses an ESP32, voice recognition module, servo motor, and lithium-ion battery. The aim of this research is to design a helmet visor opening and closing system using a microcontroller-based voice recognition module. The results of testing several human voices were not detected, of the 5 (five) people who carried out commands, only 3 (three) people received a response from the module. Noise levels also affect the module's ability to receive commands. Testing the entire system shows that the system created can run well and as designed.